2021
DOI: 10.3390/nano11102564
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-Resistant Nanocoatings Based on ZnO Nanoparticles and Linalool

Abstract: Biofilms represent an increasing challenge in the medical practice worldwide, imposing a serious threat to public health. As bacterial strains have developed antibiotic resistance, researcher’s attention has been extensively focused on developing more efficient antimicrobial strategies. In this context, the present study reports the synthesis, physicochemical characterization, ex vivo biodistribution, and in vitro evaluation of the capacity of nanostructured surfaces based on zinc oxide (ZnO) and biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Various nanostructures, such as micelles, liposomes, dendrimers, metallic NPs, and nano-coatings, have been utilized in the development of nanotechnology, especially in the biomedicine field [ 12 , 13 , 14 , 15 , 16 ]. Among the various known NPs, metal or metal oxide NPs are the most promising ones due to their antibacterial properties in association with a high surface-to-volume ratio [ 17 ].…”
Section: Types and Methods Of Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Various nanostructures, such as micelles, liposomes, dendrimers, metallic NPs, and nano-coatings, have been utilized in the development of nanotechnology, especially in the biomedicine field [ 12 , 13 , 14 , 15 , 16 ]. Among the various known NPs, metal or metal oxide NPs are the most promising ones due to their antibacterial properties in association with a high surface-to-volume ratio [ 17 ].…”
Section: Types and Methods Of Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Metal oxide nanorods and nanowires based photocatalytic coatings have attracted recent attention owing to its ease of controlled fabrication processes (Wei et al, 2005;Inderan et al, 2015;Jin et al, 2015a;Jin et al, 2015b;Wang et al, 2018). ZnO nanorod-based photocatalytic coatings have been found effective against micro-and macro-fouling on a glass substrate and fishing net substrates in the laboratory (Al-Fori et al, 2014;Spirescu et al, 2021) and field experiments, respectively (Sathe et al, 2017) (Figure 8). ZnO nanorods have increased stability, reduced loss of nanoparticles compared to ZnO nanoparticles and can be fabricated into various types of support materials (Al-Fori et al, 2014).…”
Section: Metal Oxides and Metal/metal Oxide Hybrid Nanostructurementioning
confidence: 99%
“…Nanostructured metal oxide, like ZnO and TiO 2 , is capable of absorbing visible and ultraviolet light and inhibiting microbial growth due to the photocatalytic process leading to redox reactions (Baruah et al, 2012;Danwittayakul et al, 2018;Spirescu et al, 2021). The generated reactive oxygen species (ROS) like peroxides, superoxides, and hydroxyl radicals that form during photocatalysis, prevent the growth of microorganisms on the surfaces (Sathe et al, 2017;Ganguly et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies indicate the antibacterial activity of all three components with controlled release of the antibiotic. Spirescu et al [ 36 ] developed biofilms based on ZnO and linalool NPs. In vitro assays for prokaryotic cells have shown that biofilms prevent the formation of both gram-positive and gram-negative bacterial strains.…”
Section: Introductionmentioning
confidence: 99%